Morpho-molecular diversity analysis of indigenous rice (Oryza sativa) germplasm - KUMARI, SARITA; SATYAN; SHARMA, V K; SINGH, ASHUTOSH; SINGH, SUMEET KUMAR (The Indian Journal of Agricultural Sciences, 2025)
Wild relatives of crops serve as the reservoir of kingpin genes related to various agronomic traits that play a significant role in crop improvement for sustainable agriculture. However, bequeathing these genes from wild rice has often been compromised due to climate change and anthropogenic activities posing serious threats to their natural habitats, leading to erosion of diversity. The experiment was carried out during 2021–2023 at Dr. Rajendra Prasad Central Agricultural University, Samastipur, Bihar aimed to study the utility of ISSR markers for genetic diversity analysis, population stratification, and identification of suitable donors for using in breeding programme for yield and climate resilience in rice (Oryza sativa L.). The results suggested that ISSR markers are highly informative for diversity analysis in rice. These markers showed a high level of polymorphism (85.40%) with high Polymorphic Information Content, Marker Index, and Resolving Power. ISSR markers; UBC807, UBC812, and UBC841 were identified as highly informative markers for rice. Two subpopulations were identified based on parametric and non- parametric approaches for population characterization, having the potential to be used in marker-trait association studies. Germplasms NKSWR 372, NKSWR 457, NKSWR 126, and NKSWR 245 exhibited superior agronomic performance comparatively. These elite genotypes may be utilized as potential donor for various rice improvement programmes.